2015
DOI: 10.4317/jced.52570
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diagnostic accuracy and dimensional measurements by using CBCT in mandibular first molars

Abstract: Background This study aimed to assess the diagnostic accuracy of cone beam computed tomography (CBCT) and quantitatively evaluate the morphology of mandibular first molars using CBCT. Material and Methods Twenty-four double-rooted mandibular first molars were evaluated by NewTom VGi CBCT. The distance from the furcation and apex to the cementoenamel junction (CEJ), diameter and thickness of canal walls, the buccolingual (BL) to mesiodistal (MD) ratio (ΔD), prevalence of oval canals at different sections and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…) and is an effective method for quantitatively evaluating the morphology of root canals in mandibular molars ex vivo (Asgary et al . ). In the present study, Vertucci type IV canals (independent canals with separated exits) were found in 44% of the roots, whilst in 54%, a confluence and a single apical foramen were detected (Vertucci type II).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and is an effective method for quantitatively evaluating the morphology of root canals in mandibular molars ex vivo (Asgary et al . ). In the present study, Vertucci type IV canals (independent canals with separated exits) were found in 44% of the roots, whilst in 54%, a confluence and a single apical foramen were detected (Vertucci type II).…”
Section: Discussionmentioning
confidence: 97%
“…The present results clearly indicate that the instrumentation strategy should be adjusted in every case to follow the unique anatomy of each canal (Asgary et al . ), rather than using a generalized assumption of which is the most complex canal. The proposed scoring system provides a simple guide to determine preoperatively which mesial canal is more complex when a confluence is present.…”
Section: Discussionmentioning
confidence: 99%
“…The techniques' various limitations, such as only a two-dimensional image, high cost, high time consumption, or the required destruction of the specimens,[ 10 ] have made the CT scan as the method of choice for numerous authors. [ 7 10 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although the results did not show that 3D measurements were more accurate than the 2D standard digital lateral cephalograms, the results did confirm that 3D measurements were more reliable than measurements on 2D images. According to Asgary et al .,[ 17 ] CBCT has acceptable diagnostic accuracy for measurement of canal wall thickness. Anter et al .…”
Section: Discussionmentioning
confidence: 99%